Challenges in Machine Translation For Teaching Arabic Language/ Ø§Ù„ØªØ±Ø¬Ù…Ø© Ø§Ù„ØØ§Ø³ÙˆØ¨ÙŠØ© ÙˆØ§Ù„ØªØØ¯ÙŠØ§Øª ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Khan, Lubna Farah (Ijaz Arabi Journal of Arabic Learning, 2020)
The study aims to search for syntax errors in machine translation. The study focuses on challenges in English Arabic Machine translation, types of errors in translation software, the most developed technologies in machine translation, and arbitrary Arabic text generating problems generally and in the Arabic language. This study use qualitative research design, qualitative data, drawn from our pragmatic analysis are presented, from perceptions of language learners and tutors in relation of Machine translation. The article discusses the disappointing fact that most intelligent machines are built to produce woodenly literal or paraphrased translations, but in Arabic, the errors are in high numbers. The paper results show an urgent need to build the machine language infrastructure in the Arabic language field to help people achieve accurate translation. To overcome the problems of machine translation, we recommend that we enter enough vocabulary and linguistic texts in the machine.